Visitação e turismo em Parques Nacionais : o caso do Parque Nacional da Restinga de Jurubatiba (RJ) - Botelho, Eloise Silveira (2018)
This work investigates the potential of visitation and tourism in the Restinga de Jurubatiba National Park (PNRJ), managed by the Chico Mendes Institute for Biodiversity Conservation (ICMBio), analyzing the possibilities of framing a "situated tourism" in the perspective of the theory of "symbolic sites of belonging". The study relied heavily on both bibliographical and field research to identify a significant set of strategic actors for such proposal. This involved direct observation at events and meetings, organization of workshops with interlocutors, visits to sites and semistructured interviews. The actors identified as potential protagonists of a situated tourism were the group of entrepreneurs "Ambassadors of Jurubatiba", an association linked to Quilombo Machadinha and groups of artisanal fishermen of the Carapebus Lagoon. Finally, the study proposes the possibility of ICMBio to develop an innovative management on the site, acting as an articulating agent for the development of "situated tourism" in partnership with the protagonism of local communities, and making the Campos - Macaé Canal the integration vector of a complex of "symbolic sites of belonging" that goes beyond the limits of the PNRJ itself.